NOVEL COMBINATION OF THE ANGIOTENSIN CONVERTING ENZYME INHIBITOR PERINDOPRIL AND HIGHLY SELECTIVE β-ADRENOBLOCKER BISOPROLOL: PRIME AMONG THE EQUAL - O. D. Ostroumova; A. I. Kochetkov; A. V. Starodubova; Т. F. Guseva (Кардиоваскулярная терапия и профилактика, 2018)
The article is focused on a broad evidence of antihypertension efficacy of perindopril and bisoprolol. The issues considered, of the drugs usage in patients with arterial hypertension, ischemic heart disease and chronic heart failure according to the international and local clinical guidelines. Special attention is paid for the influence of perindopril and bisoprolol on prognosis — the risk of cardiovascular complications from the evidence based medicine perspective. The data provided on a novel unique combination of these medications, and the benefits are accounted, as the mechanism of complimentary interaction; the results of randomized trials, clinical trials provided, that point on the high potential of this sort of combinational treatment.